Student-Centered Debate Techniques in Teaching English for Non-Language Majors - Sharopova Shahlo Kahramonovna; Yusupova Shirinoy Ortiqali Qizi (PT. Pusmedia Group Indonesia, 2025)
Traditional teacher-centered approaches in English language instruction prove insufficient for developing the complex communicative competencies required by students in STEM and professional programs. As professional communication demands continue to evolve in globalized contexts, there is an urgent need for innovative pedagogical approaches that create authentic communicative situations while leveraging students' existing disciplinary expertise. This mixed-methods study investigated the implementation of student-centered debate techniques among 240 undergraduate and graduate students across engineering, medical, business, and natural science programs at three universities. The intervention incorporated discipline-relevant debate topics, scaffolded preparation processes, and collaborative learning structures, with data collected through pre- and post-intervention oral proficiency assessments, classroom observations, and qualitative interviews. Results demonstrated statistically significant improvements of 1.2 Common European Framework sub-levels in overall communicative competence, with particularly notable gains in fluency, lexical sophistication, and spontaneous use of complex grammatical structures. Qualitative analysis revealed enhanced critical thinking capabilities, increased student motivation, and successful development of transferable professional communication skills, with 78% of participants applying debate-acquired skills in real-world contexts within six months. Student-centered debate techniques offer significant potential for enhancing English instruction in STEM and professional contexts by creating meaningful connections between language learning and students' academic interests, suggesting the need for institutional support, comprehensive teacher training, and curriculum integration to maximize educational outcomes.